Climate Data Tool for Regional Meteorological Service Center Data and Climate Experts - Teshome, Asaminew; Faniriantsoa, Rija (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The National Meteorological Agency (NMA), in collaboration with the International Research Institute for Climate and Society (IRI), has embarked on Enhancing National Climate Services. The initiative aims to bring climate knowledge into national decision-making by improving the availability, access, and use of climate information. These new data sets have been used to develop. The purpose of the training was to provide the necessary basis use of the IRI Climate Data Tools (CDT) to generate and exploit ENACTS datasets. A brief official opening ceremony preceded the workshop on the morning of August 16, 2021. The opening remarks were presented by Mr. Henok Hailu, Meteorological Service Centers Coordination Office Directorate Director. Representatives of IRI also attended the ceremony. The training brought together 35 participants, 10 Regional meteorological center expertise (2 from each region), and four from head office from meteorological service centers' data and climatology section. The objective of the NMA is to investigate and study the weather and climatic condition of Ethiopia to achieve beneficial effects for economic and social development. The Climate Data Tool (CDT) is a powerful instrument for quality control of station data, merging station data with satellite and other proxies, and processing station and gridded data. CDT was an essential resource for Climate data for gridded data outputs, down manipulation, data extraction, spatial and temporal analysis, rainy dekadal, monthly, season, annual characteristics, and climate extremes indices like drought and flood events. NMA is the first in Africa to apply the application and interpretation of high-resolution map products and reach merged data for different socio-economic activities of the community on using CDT products. The workshop was conducted using a participatory approach with a mix of PowerPoint presentations and the participants having ample hands-on time exploring the tool.